Dampak Pembuangan Sampah di Pesisir Pantai Terhadap Lingkungan - Walter J. Wetangamarang; Melki Imamastri Puling Tang; Trisnawati Daik; Reny Tiansi Buling; Welhelmina R. Laumalay; Yahfet K. Hamap; Trijeli H. Hinaoli; Yusti D. Sailana (Lembaga Pengembangan Kinerja Dosen, 2023)
Garbage is something that is produced from human activities and then is not used and then thrown away. Coastal waste has become a global problem and is an issue that is being widely discussed. This is because coastal waste has an impact on the environment, the economy, and human health. To be able to overcome the problem of waste, three aspects are needed, namely government, society, and waste management procedures. This study aims to determine the impact of waste disposal on the coast to the surrounding environment. The type of research used in this study is a descriptive research type with a qualitative approach that refers to data in the form of words that have clear and definite characteristics.